ANALISIS PENGARUH VARIABEL KINERJA BANK (CAR, ROA, BOPO DAN LDR), SERTA PERTUMBUHAN KREDIT DAN KUALITAS KREDIT TERHADAP NON PERFORMING LOAN (NPL) - Kusuma, Ervinna Chandra; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2016)
Credit is the main activity and used to be the largest source of income for the Conventional Commercial Bank, so it requires more attention for the crediting activity when considering that any banking activity is always exposed to various risks. Even though the bank's management has made various efforts to control the lending process, the banks potentially exposed by credit risk. This study aimed to examine the effect of CAR, ROA, ROA, LDR, Credit Growth and Credit Quality to the Non-Performing Loan (NPL). This study used a population of 120 commercial banks in Indonesia on period 2013-2015. Based on purposive sampling, obtained a sample of 12 bank which has NPL ratio above 5% for at least three quarters in the study period. The analytical method used in this research is Multiple Linear Regression Analysis. Based on test results, LDR and Credit Growth showed a negative relationship with Non-Performing Loan (NPL), but these variables have no significant effect on Non-Performing Loan (NPL), while CAR, ROA and BOPO have negative significantÂ effect on the Non-Performing Loan (NPL). Credit quality with proxied by Loan Loss Provision (LLP)Â ratio has significant positive effect on the Non-Performing Loan (NPL).